Association between B-lymphocyte membrane immunoglobulin and multiple members of the Src family of protein tyrosine kinases. - Campbell, M A (1992)
Treatment of B lymphocytes with antibodies to membrane immunoglobulin (Ig) stimulates protein tyrosine phosphorylation. We have examined the phosphorylation in vitro of proteins associated with membrane Ig. The Src family protein tyrosine kinases p53/56lyn, p59fyn, and p56lck are associated with membrane Ig in spleen B cells and B-cell lines and undergo phosphorylation in vitro. The pattern of expression of Src family protein tyrosine kinases in B cells varied. Our studies suggest that multiple kinases can potentially interact with membrane Ig and that within any one B-cell type, all of the Src family kinases expressed can be found in association with membrane Ig. We also observed that the Ig-associated Ig alpha protein, multiple forms of Ig beta, and proteins of 100 and 25 kDa were tyrosine phosphorylated in vitro. The 100- and 25-kDa proteins remain unidentified.